2020
DOI: 10.1177/2333721420981327
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Attendance and Potential Benefits of Reducing Sitting Time for Residents in a Canadian Long-Term Care Setting: A Pilot Study

Abstract: Background: This study aimed to assess the attendance to a novel intervention aiming to reduce sitting time in a long-term care facility and exploring the potential functional benefits. Methods: The intervention consisted of research staff visiting a resident to promote standing for 10-minute sessions, three times per day (morning, afternoon and evening), 4 days per week (Monday-Wednesday-Friday and Sunday) over 10 weeks. The main outcome was attendance. Functional outcomes included walking speed, power, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
1
1
Order By: Relevance
“…(23) This suggests that residents of LTC facilities with a higher functional capacity might benefit from this type of intervention. Our findings contradict the conclusions made from a standing pilot study with the same population by Lee et al (7) where it was concluded that a standing intervention might be more beneficial among LTC residents who are frailer and need assistance to transfer as they have less standing exposure.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…(23) This suggests that residents of LTC facilities with a higher functional capacity might benefit from this type of intervention. Our findings contradict the conclusions made from a standing pilot study with the same population by Lee et al (7) where it was concluded that a standing intervention might be more beneficial among LTC residents who are frailer and need assistance to transfer as they have less standing exposure.…”
Section: Discussioncontrasting
confidence: 99%
“…( 5 , 6 ) Only a few studies have examined the impact of reducing sedentary behaviour on the risk of falls among older adults living in a LTC facility. As previously reported by our group, people living in LTC facilities spend over 90% of their time engaging in sedentary behavior, ( 7 ) which may provide a window of opportunity for fall prevention interventions in this population.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation